2021
DOI: 10.1097/nnr.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Experiences of Racial Discrimination, Child Indicators of Toxic Stress, and the Minding the Baby Early Home Visiting Intervention

Abstract: Background: Racism is a significant source of toxic stress and a root cause of health inequities. Emerging evidence suggests that exposure to vicarious racism (i.e., racism experienced by a caregiver) is associated with poor child health and development, but associations with biological indicators of toxic stress have not been well studied. It is also unknown whether two-generation interventions, such as early home visiting programs, may help to mitigate the harmful effects of vicarious racism.Objective: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…children of caregivers exposed to racism have elevated levels of inflammation (Condon et al, 2021) and poor socioemotional and mental health outcomes compared with children not exposed to vicarious racism (Heard-Garris et al, 2018). Exposure to vicarious racism may also threaten a child or adolescent's sense of safety and fairness in society and bring about unintended consequences to their mental and physical health (Brody et al, 2006;Dominguez et al, 2008;Heard-Garris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…children of caregivers exposed to racism have elevated levels of inflammation (Condon et al, 2021) and poor socioemotional and mental health outcomes compared with children not exposed to vicarious racism (Heard-Garris et al, 2018). Exposure to vicarious racism may also threaten a child or adolescent's sense of safety and fairness in society and bring about unintended consequences to their mental and physical health (Brody et al, 2006;Dominguez et al, 2008;Heard-Garris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that children as young as age 3 years recognize racial groups and may display differential treatment of one another based on race (Feagin & Van Ausdale, 2001; Gee et al, 2012). Moreover, because the lives and development of children and adolescents are closely intertwined with the experiences of their family or caregivers (Heard-Garris et al, 2018), they are particularly vulnerable to vicarious racism (indirect or second-hand exposure to racism) and its effects on health (Condon et al, 2021; Heard-Garris et al, 2018). Our study found that over 50% of YMSM experienced vicarious racism in their lifetime, and such exposure was associated with increased levels of perceived stress, after controlling for race/ethnicity and other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations